Analysis of Justice to the oppressed in Mughal’s Period - Najma Parveen; Dr. Mohsina Munir** (jihat-ul-islam, 2020)
The attributes of Hindu rulers in the Indian subcontinent that led to their downfall were their cruel and abusive attitudes which first inflicted their own religions and compatriots. Hindu oppressors ruled their oppressors in every way. This was the practice of the rulers of India at the time of the arrival of the Muslims. On the contrary, the Muslim traditions here gave the oppressed the right to both the end of the atrocities and to the oppressed. Thus, not only did the concessions delight them, but Islam became the largest religion here. Examples can be exemplified, especially in the context of the Mughal rulers who did not rule for long, simply by force, but by providing justice to the concessions, which seemed always busy for their happy life. The Mughal government has uniquely positioned itself in the history of books in the management of oppression. This paper aims to highlight the practical efforts of Mughal emperors in this regard with the help of authentic historic evidences.